2012
DOI: 10.1111/j.1365-294x.2012.05523.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple biogeographical barriers identified across the monsoon tropics of northern Australia: phylogeographic analysis of the brachyotis group of rock‐wallabies

Abstract: The monsoon tropics of northern Australia are a globally significant biodiversity hotspot, but its phylogeography is poorly known. A major challenge for this region is to understand the biogeographical processes that have shaped the distribution and diversity of taxa, without detailed knowledge of past climatic and environmental fluctuations. Although molecular data have great potential to address these questions, only a few species have been examined phylogeographically. Here, we use the widely distributed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 79 publications
4
81
1
Order By: Relevance
“…Finally, when the resources required for fieldwork in the Kimberley are available (especially for wet season work), researchers have until recently tended to focus on the more diverse and topographically complex mesic regions of the north-west Kimberley (Miles & Burbidge 1975;Burbidge & McKenzie 1978;Doughty et al 2012;Palmer et al 2013). Although the Kimberley is widely recognised as a centre of biological endemism (Cracraft 1991;Slatyer et al 2007;Bowman et al 2009;Powney et al 2010), a sense of how complex and varied patterns of intraregional diversity in this area are only just beginning to develop (Oliver et al 2012b(Oliver et al , 2014Potter et al 2012;Catullo et al 2014). Recent molecular work suggests that in addition to O. murrumanu sp.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, when the resources required for fieldwork in the Kimberley are available (especially for wet season work), researchers have until recently tended to focus on the more diverse and topographically complex mesic regions of the north-west Kimberley (Miles & Burbidge 1975;Burbidge & McKenzie 1978;Doughty et al 2012;Palmer et al 2013). Although the Kimberley is widely recognised as a centre of biological endemism (Cracraft 1991;Slatyer et al 2007;Bowman et al 2009;Powney et al 2010), a sense of how complex and varied patterns of intraregional diversity in this area are only just beginning to develop (Oliver et al 2012b(Oliver et al , 2014Potter et al 2012;Catullo et al 2014). Recent molecular work suggests that in addition to O. murrumanu sp.…”
Section: Discussionmentioning
confidence: 99%
“…2011; Potter et al. 2012). Many studies have highlighted the importance of the Carpentarian barrier in shaping species distribution and diversification (Cracraft 1986; Cardinal and Christidis 2000; Jennings and Edwards 2005; Lee and Edwards 2008; Kearns et al.…”
Section: Discussionmentioning
confidence: 99%
“…2012). The regional climate is characterized by dry winters and wet summers, which has a strong effect on the distribution of plant and animals species (Bowman et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potter et al (2012) recently identified a new potential biogeographic barrier in the central Kimberley -the East-West Kimberley Divide. Adolphus is the only island we sampled that is located on the eastern side of this barrier (see Eldridge et al 2011).…”
Section: Patterns In Assemblage Compositionmentioning
confidence: 99%